Matrix Converter for PMSG based WECS Using Duty Ratio Based Switching with FOC - Gopa Kumar, S.; Ansfer, A. George (Asian Journal of Electrical Sciences, 2014)
This paper presents the direct AC to AC converter for Permanent Magnet Synchronous Generator (PMSG) based wind urbine. The direct AC to AC matrix converter is intended between the PMSG wind turbine and the grid. The power generated by the wind turbine is synchronized with the grid parameters through the converter. A modulation scheme based on duty ratio is proposed. Depending upon the duty ratio the switching of matrix converter is done. Conventional ACDC- AC back to back converter is replaced by direct AC to AC converter. The modulation scheme can be also implemented using Field Programmable Gate Array (FPGA) so that the computational speed can be improved. The machine side control is done by Field Oriented Control (FOC). A three phase to three phase matrix converter is simulated using MATLAB simulink software and the results are shown.